Некоторые итоги сравнительно-анатомического изучения стопы балерин и артистов балета - Пелипенко, В.И. (Вестник зоологии, 1973)
As a result of analysing a series of radiograms of foot new data are obtained on specific effect of an increased loading on the development of different elements of foot in ballet-dancers. The sequence of differentiation in elements of foot skeleton and succession of ossification of its epiphysial cartilages observed in the students of choreographic school are very similar to those in unguligrade and digitigrade mammals.